المراقبة الالكترونية كبديل للعقوبة السالبة للحرية قصيرة المدة - سعود, أحمد (جامعة الوادي University of Eloued, 2018)
ملخص: يتناول هذا المقال موضوعا يتعلق بنظام المراقبة الإلكترونية كبديل للعقوبة السالبة للحرية قصيرة المدة، ولقد ركّزت في بحثي على تعريفه و تبيان الشروط الواجب توفرها لتطبيقه، مع تقييم القيمه العقابية له، مُركّزا على ما جاء به التشريع الفرنسي، والقانون 18-01 المتمم للقانون رقم 05-04 المتضمن قانون تنظيم السجون وإعادة الإدماج الاجتماعي للمحبوسين. Abstract: This article deals with the subject of the electronic surveillance system as an alternative to the penalty of short-term freedom. In my research, I focused on its definition and the conditions that must be applied for its application, with an assessment of its punitive value based on the French legislation. The decree 18-01 which completes the latter decree 05-04 that includes the law of organizing prisons and Social Reintegration of Detainees.
Keywords: المراقبة الإلكترونية - السوار الإلكتروني – الحبس قصير المدة - العقوبات البديلة; Electronic Surveillance - Electronic Bracelet – Short-Term Imprisonment - Alternative Penalties.